MODEL KOOPERATIF TIPE PREVIEW QUESTION READ REFLECT RECITE REVIEW TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SD - Tikawara, Anggela; Utami, Sri; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine mastery of the effect of the application of Type preview question read reflect recite review variation on math learning on learning outcomes of the fourth grade students of SDN 16 Pontianak South?". The method used is the quasi-experiment research design used is Non- Equivalent Control Group Design . The sample of this research is class IVA ( experimental class ) amounted to 27 people and IVB grade students ( grade control ) , amounting to 28 people . The results of the analysis of data obtained by the average post-test experimental class was 79.83 and the average post-test control class is 66.76 . Concluded that there are differences in student learning outcomes which apply skills hold variation ( experimental class ) with skills that do not fully implement the holding of variation ( control class ) . From the results perhitung effect size ( ES ) ES obtained was 0.78 ( moderate criterion ) . This means that the application of the Type preview question read reflect recite review a variation on the math learning effect being on learning outcomes Elementary School fourth graders country 16 Pontianak South.Keywords : Skills of teachers Held a variation, Learning Social Sciences,Â  Learning Outcomes.